2013
DOI: 10.3109/09638288.2013.788217
|View full text |Cite
|
Sign up to set email alerts
|

Body, coping and self-identity. A qualitative 5-year follow-up study of stroke

Abstract: Stroke survivors suffered considerable ongoing and changing difficulties in relation to disability, self-perception and to coping with a new life. This continuous process of change could be seen to drain their energy. The study shows that many survivors live a more home-centred life with fewer social relations and less active participation in their community. This can entail the risk of depression and loneliness. The study also shows, however, that adopting an optimistic approach to life can lead to continued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
112
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(123 citation statements)
references
References 28 publications
7
112
1
Order By: Relevance
“…Hilton's study 15 was conducted 12 years ago and enrolled only women who had survived from stroke one year before. In the other phenomenological study, 16 the themes were: body experiences, coping, and altered life. The results of this study are also somewhat similar to our findings in relation to the themes of a deeply changed life and slowed lives, since changes and slowness in our participants sometimes referred to changes of the body.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hilton's study 15 was conducted 12 years ago and enrolled only women who had survived from stroke one year before. In the other phenomenological study, 16 the themes were: body experiences, coping, and altered life. The results of this study are also somewhat similar to our findings in relation to the themes of a deeply changed life and slowed lives, since changes and slowness in our participants sometimes referred to changes of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this time, they are more likely to be focused only on the meaning of physical disability, and only later can they also focus on the meaning of other aspects of daily life and family interactions 25 Other authors have also investigated the lived experiences of stroke survivors with qualitative methods but we found only two published studies in the last 12 years that used a phenomenological perspective to uncover the meaning of the 'whole' experience of stroke. 15,16 The first study 15 was conducted with five female survivors one year after the stroke and the investigators found the overarching theme of transformations which was interwoven with six other themes, which were dawning awareness of self as disabled, life and suffering through inexorable losses, quest for self, adaptation to change, existential reestablishment of self, reconciliation and re-engagement. These themes are similar to the experiences our stroke survivors described in the themes of a deeply changed life and slowed lives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations